Huge Intravascular Tumor Extending to the Heart: Leiomyomatosis - Suat Doganci; Erkan Kaya; Murat Kadan; Kubilay Karabacak; Gökhan Erol; Ufuk Demirkilic (Case Reports in Surgery)
Intravenous leiomyomatosis (IVL) is a rare neoplasm characterized by histologically benign-looking smooth muscle cell tumor mass, which is growing within the intrauterine and extrauterine venous system. In this report we aimed to present an unusual case of IVL, which is originating from iliac vein and extended throughout to right cardiac chambers. A 49-year-old female patient, who was treated with warfarin sodium due to right iliac vein thrombosis, was admitted to our department with intermittent dyspnea, palpitation, and dizziness. Physical examination was almost normal except bilateral pretibial edema. On magnetic resonance venography, there was an intravenous mass, which is originated from right internal iliac vein and extended into the inferior vena cava. Transthoracic echocardiography and transesophageal echocardiography revealed a huge mass extending from the inferior vena cava through the right atrium, with obvious venous occlusion. Thoracic, abdominal, and pelvic MR showed an intravascular mass, which is concordant with leiomyomatosis. Surgery was performed through median sternotomy. A huge mass with 25-cm length and 186-gr weight was excised through right atrial oblique incision, on beating heart with cardiopulmonary bypass. Histopathologic assessment was compatible with IVL. Exact strategy for the surgical treatment of IVL is still controversial. We used one-stage approach, with complete resection of a huge IVL extending from right atrium to right iliac vein. In such cases, high recurrence rate is a significant problem; therefore it should be kept in mind.